2017
DOI: 10.3389/fmicb.2017.01189
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the Rumen Ciliate Entodinium caudatum by Antibiotics

Abstract: Axenic cultures of free-living aerobic ciliates, such as Tetrahymena thermophila and Paramecium aurelia, have been established and routinely used in laboratory research, greatly facilitating, or enabling characterization of their metabolism, physiology, and ecology. Ruminal protozoa are anaerobic ciliates, and they play important roles in feed digestion and fermentation. Although, repeatedly attempted, no laboratory-maintainable axenic culture of ruminal ciliates has been established. When axenic ciliate cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 59 publications
(68 reference statements)
0
43
0
Order By: Relevance
“…Glycogen accumulation in En. caudatum was associated with inhibition by antibiotics (Park et al, 2017). Glycogenesis was probably an indicator, not a cause.…”
Section: Interactions Of Protozoa With Other Community Members Interamentioning
confidence: 91%
See 4 more Smart Citations
“…Glycogen accumulation in En. caudatum was associated with inhibition by antibiotics (Park et al, 2017). Glycogenesis was probably an indicator, not a cause.…”
Section: Interactions Of Protozoa With Other Community Members Interamentioning
confidence: 91%
“…For example, En. caudatum lacks a hydrogenosome (Park et al, 2017) and does not consistently shift fermentation toward butyrate as shown with mixing monofaunated cultures (Zeitz et al, 2013). Defaunation in vivo is typically associated with a decrease in molar ratio of butyrate (Newbold et al, 2015).…”
Section: Interactions With Fungi and Archaeamentioning
confidence: 99%
See 3 more Smart Citations